The European Rescue of the Washington Consensus? EU and IMF Lending to Central and Eastern European Countries - Susanne Lütz; Matthias Kranke (London School of Economics and Political Science (LSE), European Institute, 2010)
The latest global financial crisis has allowed the International Monetary Fund (IMF) a spectacular comeback. But despite its notorious reputation as a staunch advocate of restrictive economic policies, the Fund has displayed less preference for austerity in recent crisis lending. Though widely welcomed as overdue, the IMF's shift away from what John Williamson coined the 'Washington Consensus' was met with resistance from the European Union (EU) where it concerned Central and Eastern European (CEE) countries. The situation of hard-hit Hungary, Latvia, and Romania propelled unprecedented cooperation between the IMF and the EU, in which the EU has very actively promoted orthodox measures in return for loans. We argue that this represents a European rescue of the Washington Consensus. The case of Latvia is paradigmatic for the profound disagreements between an austerity-demanding EU and a less austere IMF. The IMF's stance contradicts conventional wisdom about the organization as the guardian of economic orthodoxy. To solve this puzzle, we shed light on three complementary factors of (non)learning that have shaped the EU's relations vis-à-vis CEE borrowing countries in comparison to the IMF's: (1) a disadvantageous institutional setting; (2) vociferous creditor coalitions; (3) the precarious eurozone project.
Keywords: 330; International Monetary Fund (IMF); European Union (EU); Washington Consensus; lending; learning; Central and Eastern Europe (CEE); Latvia